The first minutes in the life of a peroxisomal matrix protein - Dias, AF (2016)
In the field of intracellular protein sorting, peroxisomes are most famous by their capacity to import oligomeric proteins. The data supporting this remarkable property are abundant and, understandably, have inspired a variety of hypothetical models on how newly synthesized (cytosolic) proteins reach the peroxisome matrix. However, there is also accumulating evidence suggesting that many peroxisomal oligomeric proteins actually arrive at the peroxisome still as monomers. In support of this idea, recent data suggest that PEX5, the shuttling receptor for peroxisomal matrix proteins, is also a chaperone/holdase, binding newly synthesized peroxisomal proteins in the cytosol and blocking their oligomerization. Here we review the data behind these two different perspectives and discuss their mechanistic implications on this protein sorting pathway. This article is part of a Special Issue entitled: Peroxisomes edited by Ralf Erdmann.